Enhancing the Catalytic Activity of Pd Nanocrystals towards Suzuki Cross-Coupling by g-C3N4 Photosensitization - Mondal, Sanjit; Sahoo, Lipipuspa; Banoo, Maqsuma; Vaishnav, Yuvraj; Prabhakaran Vinod, Chathakudath; Gautam, Ujjal (Chemnanomat, 2024)
Developing renewable means of activating molecules over traditional catalysts for C-C bond formation is desirable for industrial applications. Herein, we report a strategy to improve the efficiency of Pd nanoparticles (NPs) for the Suzuki cross-coupling reactions by visible-light irradiation using g-C3N4 nanosheets (NSs) as photosensitizer. Pd NPs mounted on g-C3N4 become electron-rich under visible-light due to generation of excited electrons in g-C3N4 and thereby accelerate the rate-determining step. Remarkable photocatalytic activity was accomplished utilizing Pd/g-C3N4 for the Suzuki cross-coupling reaction in environmentally benign aqueous settings under room temperature conditions. The activity remarkably improves (similar to 2.5 times) upon light irradiation, yielding one of the highest known turnover frequencies (TOF) of 1858 h(-1) and confirming the photosensitizer role of g-C3N4. The TOF for coupling of aryl bromides is also significantly high (similar to 356 h(-1)). We establish that the low-energy/long-lived excitons preferencially transfer to Pd, paving a way for rational designing photocatalysts for various C-C coupling reactions.
Keywords: 2D graphitic carbon nitride; C-C cross-coupling; exciton transfer; heterogeneous photocatalyst; Photosensitization